Life is beautiful - Benigni, Roberto; Braschi, Nicoletta, 1960-; Durano, Giustino, 1923-; Cerami, Vincenzo, 1940-2013.; Miramax Home Entertainment (Firm); Buena Vista Home Entertainment (Firm); Miramax Films ([Burbank, CA] : Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 1997)
A charming but bumbling waiter who's gifted with a colorful imagination and an irresistible sense of humor has won the heart of the woman he loves and has created a beautiful life for his young family. But then, that life is threathened by World War II, and his beloved wife and son are threatened with an unthinkable fate.
Originally produced as a motion picture in 1997 in Italian language under Italian title: La vita e bella.
Includes "Making life beautiful" featurette, Academy Award TV commercials, and theatrical trailer.
MPAA rating: PG-13.
Director of photography, Tonino Delli Colli ; film editor, Simona Paggi ; music by Nicola Piovani.
Roberto Benigni, Nicoletta Braschi, Giutino Durano, Sergio Bustric, Giuliana Lojodice, Amerigo Fontani, Pietro De Silva, Francesco Guzzo, Raffaella Lebboroni, Giorgio Cantarini ; English voice cast: Jonathan Nichols, Ilaria Bonnelli, James Falzone, Sam Fontana, Chip Bolcik, Nicholas Kepros, Horst Buchholz.
Young Adult
Keywords: World War, 1939-1945 -- Fiction; Holocaust, 1933-1945 -- Fiction; Closed caption video recordings; Videodiscs; Jews -- Italy -- Drama; Concentration camps -- Drama; World War, 1939-1945 -- Italy -- Drama; Foreign films -- Italy; Video recordings for hard of hearing people; Feature films; DVD-Video discs; Feature films